2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe) 2016
DOI: 10.1109/epe.2016.7695577
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive discontinuous zero sequence signal for modular multilevel converter applications

Abstract: This work proposes a technique to inject a discontinuous zero sequence signal (D-ZSS) into voltage modulation of the modular multilevel converter arms. The core of the technique is the clamping of the arm voltages to a particular level and interval, in such a way that reduces the number of switching events on the instants that the load stress on the semiconductors is high, and consequently the dissipated energy. The clamping voltage and interval has some degrees of freedom which are also discussed. The descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the discontinuous ZSS an offset is added to the modulation index target in such a way that voltage generated at the VSC's output is clamped to a particular voltage level. In the literature it is shown that its possible to clamp the converter voltages over 30, 60, and 120 degrees intervals [33,34,47], and during those intervals the switching events are avoided [48,49]. The impact of the combination between the modulation techniques and the ZSS presented on the modular multilevel converter performance was also analyzed and presented in Section 4.…”
Section: Discontinuous Zss (D-zss)mentioning
confidence: 99%
“…In the discontinuous ZSS an offset is added to the modulation index target in such a way that voltage generated at the VSC's output is clamped to a particular voltage level. In the literature it is shown that its possible to clamp the converter voltages over 30, 60, and 120 degrees intervals [33,34,47], and during those intervals the switching events are avoided [48,49]. The impact of the combination between the modulation techniques and the ZSS presented on the modular multilevel converter performance was also analyzed and presented in Section 4.…”
Section: Discontinuous Zss (D-zss)mentioning
confidence: 99%